Effect of Nano-urea on Growth, Productivity and Economics of Transplanted Rice - Pedireddy, Sneha; Kumar, Manish; Saha, Soumya; Nag, Narendra Kumar; Chandrakar, T. P.; Singh, D. P. (International Journal of Economic Plants, 2024)
A field experiment was conducted during July to November of 2021 to assess the effect of nano-urea on growth and productivity of rice at ICAR-Indian Institute of Rice Research, Hyderabad, Telangana State, India. The experiment was laid out in randomized complete block design consisting eight treatments viz., Recommended dose of nitrogen (RDN) through urea (T1), 50% of RDN (urea)+two foliar sprays of nano-urea @ 0.2% at Active tillering (AT) and Panicle initiation (PI) stages (T2), 75% of RDN+two foliar sprays of nano-urea @ 0.2% at AT and PI (T3), 50% of RDN+two foliar sprays of nano-urea @ 0.4% at (AT and PI) (T4), 75% of RDN+two foliar sprays of nano-urea @ 0.4% at AT and PI (T5), 25% of RDN+Four foliar sprays of nano-urea @ 0.2% at 20,33,50 and 65 DAT (T6), 25% of RDN+Four foliar sprays of nano-urea @ 0.4% 20,33,50 and 65 DAT (T7) and control (no fertilizer application) (T8). Results showed that foliar spray of nano-urea resulted in higher plant height (120.1 cm), tillers number m-2 (265) and dry matter accumulation (741.9 kg ha-1). Yield attributes viz., panicle number m-2, number of grains panicle-1, number of filled grains panicle-1 were significantly influenced by the application of nano-urea. The highest grain yield (5.39 t ha-1) and straw yield (6.73 t ha-1) was recorded with the application of 75% of RDN+two foliar sprays of nano-urea @ 0.4% at AT and PI stages. The application of nano-urea resulted in saving of nitrogen (urea) to an extent of 25%.